Dengue: awareness, preventive practices and water storage behaviour in an urban community of Delhi - Arora, Priya; Arora, Manisha; Sharma, Vishal; Kotwal, Atul (International Journal Of Community Medicine And Public Health, 2017)
Background: Dengue, an arboviral disease transmitted by Aedes egypti mosquito, has become an important public health problem, with almost half the population of the world being at risk. Community awareness and involvement for vector control is an important aspect of disease prevention and control. The aims and objective was to assess awareness and preventive practices used for dengue and related water storage behaviour in an urban area of Delhi. Methods: Observational, descriptive, cross sectional study. Results: Awareness about dengue fever and its mode of spread is quite high but the participants are not aware about the practices that are putting their surroundings at risk of vector breeding; especially when it comes to water storage behaviour. Conclusions: Behaviour change at individual and community level is essential for vector and hence dengue control, adoption of proper preventive practices and water storage behaviour needs to be emphasized at the community level.